RISIKO KESEHATAN PAPARAN KERJA TERHADAP BAHAN KIMIA BERACUN DI TEMPAT KERJA TAMBANG BATUBARA - Ahmad Irfansyah; Susilawati (CV. ADIBA AISHA AMIRA, 2023)
Mining is the most dangerous occupational sector in the world. Based on statistical data from the Ministry of Energy and Mineral Resources, during 2019 there were mining accidents which resulted in the death of 24 people, 105 workers heavy and 28 workers light. The cause of work accidents in the workforce is related to exposure to underground mining toxic gases. This study used the Literature Review (LR) methodology where the data source was obtained from